Reasons for Women to Stay in Violent Dating Relationships: Literature Review - Swasti, Ni Kadek Candra; Swandi, Ni Luh Indah Desira; Wulanyani, Ni Made Swasti (Yayasan Sinergi Kawula Muda, 2023)
In reality, dating relationships are not always fill up by positive romantic relationships. There are many deviant dating behaviors that lead to cases of violence. Interestingly, although dating violence clearly has many negative impacts on various aspects, some women decide to stay in the relationship. This article aims to analyze and summarize research findings regarding the reasons for why women persist in violent dating relationships. This research uses literature study methods. Article searches were conducted through Google Scholar and Garuda with the keywords